Knowledge, attitudes and practices of the general public toward sun exposure and protection: A national survey in - Khalid M. AlGhamdi; Aeed S. AlAklabi; Abdulla Z. AlQahtani (Elsevier, 2016)
Background: Many international studies have been conducted to assess the knowledge, attitudes and practices (KAP) of the public toward sun exposure and sun-protection measures. However, there are scarce data on these factors from the Middle East. Objectives: This study aimed to explore the KAP of the public toward sun exposure and sun-protection measures among Saudis. Methods: A cross-sectional survey using a specially designed questionnaire was conducted on a stratified random sample of the general population in the five geographical regions of Saudi Arabia (central, eastern, northern, southern, and western). Data were collected between October 2010 and March 2011. Multiple logistic regressions were applied to relate the use of sunscreen and skin cancer awareness with various socio-demographic variables. Results: The questionnaire was distributed to 2900 Saudis. A total of 2622 questionnaires were completed, returned, and included in the data analysis, corresponding to a response rate of 90.4%. The mean (SD) age of respondents was 27.8 ± 9.7 years. Fifty percent (1301/1601) of the respondents were males. Fifty-five percent (1406/2544) were aware of the association between sun exposure and skin cancer. Female, young and student respondents were more likely to be aware of the connection between sun exposure and skin cancer (p < 0.001). Likewise, respondents from the middle social class and those with higher education levels were more likely to be informed (p < 0.02). The prevalence of regular sunscreen use among study participants was only 23.7%, and female and employed respondents were more likely to use sunscreen (p < 0.001). Protective clothes were the most commonly used sun protection measure as reported by more than 90% of our participants. Conclusion: This study has shown that sun awareness and protection are generally inadequate in the Saudi population and suggests the need for health education programs.